Comprehensive Intensive Care Management of Sepsis Secondary to Submandibular Abscess Complicated by Ventilator-Associated Pneumonia - Vonny, Vonny; Oktaliansah, Ezra; Erlangga , M. Erias (Journal of Society Medicine, 2026)
Introduction: Submandibular infections encompass a spectrum ranging from cellulitis and phlegmon to abscess formation, often originating from odontogenic sources. A submandibular abscess represents a localized collection of pus within the submandibular space, while phlegmon refers to a diffuse, non-suppurative inflammatory process that may precede abscess formation. These conditions pose significant clinical concern due to their proximity to vital structures and potential for rapid spread through deep neck fascial planes. If not promptly treated, such infections can spread through cervical fascial planes, resulting in complications such as mediastinitis, pulmonary infection, sepsis, multiorgan failure, and death. Early recognition and prompt management are therefore critical to prevent severe morbidity and mortality. Case Description: A 35-year-old man was referred to the emergency department for extensive bilateral submandibular and submental abscesses of odontogenic origin. The patient had previously undergone incision and drainage, tracheostomy, and odontectomy of the gangrenous mandibular molars at previous hospital. Despite these interventions, the patient developed pneumonia with purulent discharge from the tracheostomy site. Imaging revealed the extension of the infection into the parapharyngeal and retropharyngeal spaces, requiring repeat surgical debridement. Following surgery, the patient was admitted to the intensive care unit (ICU) and required mechanical ventilation. The ICU course was complicated by right-sided pleural empyema necessitating thoracotomy with decortication and chest tube placement, as well as ventilator-associated pneumonia caused by multidrug-resistant organisms. Management involved aggressive source control, advanced airway management, broad-spectrum antimicrobial therapy, optimized nutritional support and intensive respiratory physiotherapy. Conclusion: This case underscores the complexity of managing submandibular abscess complicated by sepsis and ventilator-associated pneumonia. Early recognition, prompt surgical intervention, meticulous airway management, and comprehensive multidisciplinary intensive care are crucial for improving outcomes in patients with extensive deep neck infections and critical respiratory complications.